Impact of Prolonged Operative Time on Complications in DIEP Flap Breast Reconstruction: A Single-Center Retrospective Study - Grönroos, Anniina (My University, 2026)
Autologous breast reconstruction is associated with superior long-term satisfaction and quality of life compared with implant-based approaches. Among autologous techniques, the deep inferior epigastric perforator (DIEP) flap is widely regarded as the gold standard; however, its microsurgical complexity may result in prolonged operative times. Extended surgical duration may contribute to higher complication rates, yet the specific impact of operative time on outcomes in DIEP reconstruction remains insufficiently defined. This study aimed to evaluate the effect of prolonged operative time on postoperative complications and to identify independent predictors of risk in a large single-center cohort. A retrospective analysis was performed of consecutive patients who underwent elective unilateral or bilateral DIEP flap breast reconstruction at a single center between 2009 and 2024. Patients were divided into standard and prolonged operative time groups, with prolonged time defined as greater than the 75th percentile of the cohort. Comparative analyses were conducted. Demographic characteristics and comorbidities were assessed as secondary predictor variables. The primary outcome was the occurrence of any postoperative complication, while secondary outcomes included specific wound-healing and late complications. A total of 270 patients were included in this study. Although the overall complication rates did not differ significantly between groups, prolonged operative time was associated with higher rates of total flap loss and seroma formation. Patients in the prolonged group more often had higher-risk characteristics, such as neoadjuvant chemotherapy, higher BMI, higher ASA scores, greater blood loss, and more frequent bilateral reconstructions. Multivariable analysis identified higher BMI as an independent predictor of postoperative complications. These findings suggest that while overall morbidity may be similar, prolonged operative time is linked to severe complications, highlighting the importance of careful preoperative optimization and surgical planning, especially in high-risk patients.
Keywords: Leikkausaika; vapaa kudossiirre; rintarekonstruktio; DIEP-rekonstruktio; postoperatiivinen komplikaati